Energy-efficient connected coverage of discrete targets in wireless sensor networks. (9th April 2009) - Lu, Mingming; Wu, Jie; Cardei, Mihaela; Li, Minglu
A major concern in wireless sensor networks is to maximise network lifetime (in terms of rounds) while maintaining a high Quality of Service (QoS) at each round, which includes target coverage and network connectivity. Due to the power scarcity of sensors, a mechanism that can efficiently utilise energy has a great impact on extending network lifetime. Most existing works concentrate on scheduling sensors between sleep and active modes to maximise network lifetime while maintaining target/area coverage and network connectivity. This paper generalises the sleep/active mode by adjusting sensing range to maximise the total number of rounds. Two distributed solutions have been proposed and simulation results confirm the efficiency of our solutions.